Studi Insilico Potensi Minyak Astiri dan Ekstrak Etanol Daun Annona muricata Sebagai Calon Herbal Terstandart Untuk Analgesik dan Antiinflamasi - Reza Hakim; Yoni Rina Bintari; Dini Sri Damayanti (Jurnal Kesehatan Islam : Islamic Health Journal, 2018)
ABSTRACTInflammatory reactions give rise to a series of processes and symptoms that can cause pain and damage to nearby cells. Inflammatory reactions are mediated by inflammatory and proinflammatory cytokines. NSAID class (non-steroidal anti-inflammatory drug) drugs have been developed to inhibit the inflammatory process by suppressing COX-1 and / or COX-2 enzyme activity. However, this drug can cause gastric mucosal irritation. the ethanol extract of Annona muricata leaf has an analgesic and anti-inflammatory effect[3].The purpose of this research is to know analgesic and antiinflamatory activity from ethanol extract and essential oil of Annona muricata leaf.The method used was the study of in silico by molecular docking of active compounds in ethanol extracts and essential oils to the COX-1, COX-2, phospolipase-A, and TNF-alpha receptor molecules as target molecules. The molecular docking results show that Annona muricata ethanol extract can act as an anti-inflammatory and analgesic, especially through strong bonds between "rutine" compounds with COX-2 receptors with affinity -10 kcal / mold and "quercetin" with affinity bindings -9.8 kkal.mol, better than dexametason (binding affinity -9.6 kcal / mol). Keywords:Inflamation, COX-1, COX-2, phospolipase-A, TNF-alfa, docking